Development Of Analytical Solution For Thermo-Mechanical Stresses Of Multilayered Pressure Vessel Based On Recursive Algorithm - Sim, Lih Chi (2022)
Multilayered pressure vessel is commonly used under harsh conditions, particularly in high pressure and high temperature environment. Thus, the evaluation of the stresses induced within the multilayered pressure vessel’s wall is crucial to ensure safe operation. Recent studies showed that analytical solution based on recursive algorithm can be used to obtain thermo-mechanical stresses of multilayered structure efficiently. However, there is no study has been conducted for the derivation of analytical solutions for multilayered spherical pressure vessel and cylindrical pressure vessel under generalized plane strain condition. Hence, the present work aimed to derive the analytical solution by using recursive algorithm for multilayered cylindrical and spherical pressure vessels which are subjected to thermo-mechanical loading. Firstly, the analytical solution for temperature distribution across the multilayered vessel wall was derived. Next, the analytical solutions for radial, tangential and axial stresses distribution across the multilayered vessel wall were derived. After that, verification was carried out on the proposed analytical solutions by using two finite element analysis models reported in literatures. The simulated results were in good agreement with the output from the proposed analytical solutions. In addition, the validated analytical solutions were demonstrated as the iii alternative method to analyze the stresses of functionally graded material (FGM) cylindrical and spherical pressure vessel under thermo-mechanical loading. In general, the stresses results obtained based on present proposed analytical solutions were compared with the FGM exact solution reported in literatures and the overall percentage of difference is less than 1%.